2013
DOI: 10.5935/1678-9741.20130074
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection with prophylactic oral metoprolol during coronary artery bypass grafting surgery: evaluation by troponin I

Abstract: IntroductionBiochemical markers of myocardial injury are frequently altered after cardiac surgery. So far there is no evidence whether oral beta-blockers may reduce myocardial injury after coronary artery bypass grafting. ObjectiveTo determine if oral administration of prophylactic metoprolol reduces the release of cardiac troponin I in isolated coronary artery bypass grafting, not complicated by new Q waves. MethodsA prospective randomized study, including 68 patients, divided in 2 groups: Group A (n=33, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The final 21 papers were reviewed in full text, and the following were excluded due to the following reasons: 1 study did not have a control group, 6 1 study used sotalol as its study drug, 7 1 study did not segregate outcomes between isolated AF and other forms of SVT, 8 and 1 study focused on the combination therapy of b-blocker and magnesium. 9 Eventually, 17 RCTs, 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 fully satisfying our predefined inclusion criteria, were selected from papers published in varying years. Figure 1 is the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols flow chart of our study as per established 2009 guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final 21 papers were reviewed in full text, and the following were excluded due to the following reasons: 1 study did not have a control group, 6 1 study used sotalol as its study drug, 7 1 study did not segregate outcomes between isolated AF and other forms of SVT, 8 and 1 study focused on the combination therapy of b-blocker and magnesium. 9 Eventually, 17 RCTs, 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 fully satisfying our predefined inclusion criteria, were selected from papers published in varying years. Figure 1 is the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols flow chart of our study as per established 2009 guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…All trials focused on isolated POAF for patients undergoing cardiac surgery. Eleven trials only included patients who underwent coronary artery bypass grafting (CABG) surgery, 10 , 11 , 12 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 whereas 6 other trials included patients with a variety of surgeries (CABG and valve). 5 , 13 , 15 , 23 , 24 , 25 Study characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Rossi Neto et al. [ 21 ] have shown that the preoperative use of metoprolol is associated with lower levels of troponin I, but no data regarding survival is presented. Our study reflects the outcome of a single center where almost 70% of patients were using beta-blockers previous to CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al [ 11 ] discovered significant elevated serum troponin I during the early days after the onset or surgical repair of myocardial rupture, and they advocated the troponin I was valuable in judging the prognosis of the patients with myocardial injury. Troponin I (as well as NT-BNP) can be helpful in the evaluation of the functions of the vital organs including heart subjected to perioperative drug use, such as oral prophylactic metoprolol [ 12 ] and high-dose aprotinin [ 13 ] .…”
Section: Discussionmentioning
confidence: 99%